2001
DOI: 10.1111/j.1469-7793.2001.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles of glycolysis and the mitochondrial electron transport chain in hypoxic pulmonary vasoconstriction of the rat: identity of the hypoxic sensor

Abstract: The mechanisms responsible for sensing hypoxia and initiating hypoxic pulmonary vasoconstriction (HPV) are unclear. We therefore examined the roles of the mitochondrial electron transport chain (ETC) and glycolysis in HPV of rat small intrapulmonary arteries (IPAs). HPV demonstrated a transient constriction (phase 1) superimposed on a sustained constriction (phase 2). Inhibition of complex I of the ETC with rotenone (100 nm) or complex III with myxothiazol (100 nm) did not cause vasoconstriction in normoxia, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
174
2
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(198 citation statements)
references
References 51 publications
17
174
2
5
Order By: Relevance
“…By depleting RISP, the formation of ubisemiquinone at the Qo site is prevented, thus mimicking the response to myxothiazol. Taken together, these results are also consistent with a broader body of work indicating that hypoxia increases mitochondrial ROS signaling (10,17,18,(27)(28)(29)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By depleting RISP, the formation of ubisemiquinone at the Qo site is prevented, thus mimicking the response to myxothiazol. Taken together, these results are also consistent with a broader body of work indicating that hypoxia increases mitochondrial ROS signaling (10,17,18,(27)(28)(29)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 89%
“…Our previous work has implicated increases in reactive oxygen species (ROS) signaling during hypoxia (9,10,12). Previous studies using mitochondrial inhibitors and mitochondria-deficient (r 0 ) cells suggested that the electron transport chain (ETC) is required for hypoxia-induced ROS signaling in the pulmonary circulation (9,(11)(12)(13)(14)(15)(16)(17)(18). We subsequently assessed ROS signaling in hypoxic PASMC using roGFP, a thiol-containing, redox-sensitive reporter (19)(20)(21)(22)(23) targeted to compartments within mitochondria or the cytosol (10).…”
mentioning
confidence: 99%
“…BAEC remained viable compared to the control as reported previously [25]. 2-DOG has been widely used to study intracellular redox status in pulmonary arterial endothelial cell electron transport [63,64]. Although 2-DOG was not a specific NADPH inhibitor, others such as 6-amino-nicotinamide [65] to inhibit NADPH regeneration via the pentose phosphate pathway can also be toxic and nonspecific.…”
Section: Discussionsupporting
confidence: 59%
“…2A). (21) was needed and the fact that, in isolated lungs from rats as well as in isolated pulmonary arterial rings or PASMC from different species, a ''priming'' with angiotensin II, ET-1, or PGF 2a is a prerequisite to elicit any or full hypoxic vasoconstriction (22)(23)(24). The underlying mechanism of this priming is still not resolved (for review, see ref.…”
Section: Isolation Of Pasmc and Expression Of Trpc Subtypes In Pasmcmentioning
confidence: 99%